Smoking behavior analysis on teenagers in Kulon Progo Yogyakarta - Sujono Riyadi; Sutipyo Ru'iya (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: Adolescent smoking behavior from day to day is increasing. Teenagers who initially did not smoke became smokers because the environment around them did not heed subjective norms. Coupled with the influence of smoking, families increases the power of adolescents to be negative towards smoking. Objectives: This study aimed to determine the direct or indirect effect of attitude, subjective norm, and intention on adolescent smoking behavior in Kulon Progo Yogyakarta. Methods: This research is quantitative in form, conducted in Kulon Progo Yogyakarta. The population was 59.588 adolescents, after being calculated by the Slovin formula obtained 400 samples. Variable in the form of attitude, subjective norm, intention, and smoking behavior. The data were obtained by distributing valid and reliable questionnaires to 400 respondents, 200 smokers and 200 non-smokers, then analyzed using a path analysis using Stata 13. Results: There was a direct influence on adolescent attitudes towards not smoking (p <0.001) and intention to not smoke in adolescents. (p <0.001) on smoking behavior in adolescents in Kulon Progo Yogyakarta. Conclusions: There is an indirect influence between subjective norms of not smoking through non-smoking attitudes and non-smoking intentions on smoking behavior among adolescents in Kulon Progo Yogyakarta.